Transformational prophetic leadership in building a culture of quality in higher education - M. Furqon Wahyudi; Taufiq Harris; Sri Sundari; Ahmad Hanif Fahruddin (Akademika, 2026)
This study aims to examine the role of transformational prophetic leadership in building a culture of quality in higher education. Using a qualitative case study approach, data were collected through semi-structured interviews, observations, and document analysis involving university leaders, quality assurance personnel, and academic staff. The data were analyzed using an interactive model, including data condensation, data display, and conclusion drawing. The findings reveal that transformational leadership contributes to the development of a quality culture through vision building, innovation, and active stakeholder engagement. At the same time, prophetic leadership reinforces ethical values such as honesty, trustworthiness, transparency, and wisdom, which serve as the foundation of organizational behavior. The integration of these two leadership approaches referred to as transformational prophetic leadership creates a holistic model that balances performance orientation with moral and spiritual values. Furthermore, the study shows that a sustainable culture of quality is achieved not only through formal quality assurance systems but also through leadership practices that foster trust, participation, and continuous improvement. This study contributes to the development of leadership theory by integrating transformational and value-based perspectives, and provides practical implications for higher education leaders in designing effective and ethical leadership strategies